A time for consolidation: A bibliometric analysis of L2 vocabulary research 1985–1989 - Paul Meara (LingBaW)
This paper uses a co-citation analysis to examine the research on L2 vocabulary acquisition that was published in 1989. Two analyses are presented. The first is a detailed account of the 1989 research on its own terms. The second analysis places this work in a larger context by looking at research published in a five-year window covering 1985–89. The analyses identify important themes in the research and significant sources who are influencing the way the research is developing at this time. The main features of this work are the substantial growth in dictionary and corpus research, and the emergence of Paul Nation as the Most Significant Source in 1989.